Arabic Sciences in the Studies of Nabil Ali: A Study in Conceptualization Criticism and Its Principles - Al-Dadi, Muqbil Bin Ali (Arts for Linguistic & Literary Studies, 2024)
The study addresses Nabil Ali's perspectives on Arabic language sciences, examining his perceptions of curricula, issues, and characteristics, and seeks to elucidate the underlying principles and models shaping his linguistic framework. The research is structured into an introduction and four sections: Principles and Foundations, Features of Conceptualization, Starting Points for Development, and Reviewing Conceptualization. It endeavors to reconcile Nabil Ali's views on Arabic sciences, identifying their common origins and contrasting them with the actual state of these disciplines. Findings suggest that Nabil Ali's focus is primarily on morphology and syntax, and lexicography, neglecting other branches of Arabic language studies. This narrow focus is attributed to his adherence to contemporary linguistics and the constraints imposed by computational processing requirements, resulting in an incomplete portrayal of Arabic sciences marked by scientific and cognitive inaccuracies.